(untitled) (Al-Aasar, 2025)
This paper examines the Qur’anic notion of sakīnah (tranquility) as a divinely granted state of peace and assurance. Focusing on selected Quranic passages, it explores the term’s semantic scope and theological significance, particularly its role in reinforcing faith and resilience during times of trial. The analysis draws on classical exegesis alongside contemporary scholarship to show how sakīnah functions both as an inner psychological calm and as a collective source of strength that unites and empowers the Muslim community. Rather than being limited to personal serenity, sakīnah emerges as a dynamic concept that bridges the spiritual and social dimensions of human experience. The study further underscores its continuing relevance by highlighting its implications for emotional stability, trust in God, and the cultivation of harmony in Muslim spiritual and communal life. In doing so, it positions sakīnah as a key Qur’anic principle with enduring resonance for both individual spirituality and collective well-being.